1995
DOI: 10.1037/h0089142
|View full text |Cite
|
Sign up to set email alerts
|

Filial therapy with single parents: Effects on parental acceptance, empathy, and stress.

Abstract: The rationale for filial therapy is explored and the effectiveness of a ten week filial therapy parent training group for single parents is described. Research procedures and instruments utilized are presented. Results of the analyses of covariance revealed that the single parents in the experimental group significantly increased both their attitude of acceptance and their empathic behavior toward their children, significantly reduced their level of stress related to parenting, and reported significantly fewer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
101
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(118 citation statements)
references
References 9 publications
(17 reference statements)
16
101
0
1
Order By: Relevance
“…In addition, since significant decreases were noted on the Internalizing and Withdrawn subscales of the CBC/C-T, and positive trends toward the reductions of Anxious/Depressed Behaviors were also seen on the CBC/C-T, similar reductions were expected on the Anxious/Compulsive subscale of the SEAI. Further, as it has also been well-documented that children whose parents have participated in filial therapy training have shown significantly fewer anxious behaviors in their parents' evaluation at posttesting (Smith, 2001;Bratton & Landreth 1995;Bavin-Hoffman, 1994), similar results were expected on this scale of the SEAI.…”
Section: Empathysupporting
confidence: 69%
See 2 more Smart Citations
“…In addition, since significant decreases were noted on the Internalizing and Withdrawn subscales of the CBC/C-T, and positive trends toward the reductions of Anxious/Depressed Behaviors were also seen on the CBC/C-T, similar reductions were expected on the Anxious/Compulsive subscale of the SEAI. Further, as it has also been well-documented that children whose parents have participated in filial therapy training have shown significantly fewer anxious behaviors in their parents' evaluation at posttesting (Smith, 2001;Bratton & Landreth 1995;Bavin-Hoffman, 1994), similar results were expected on this scale of the SEAI.…”
Section: Empathysupporting
confidence: 69%
“…Also, in L. Guerney and Flumen's (1970) study with teachers of withdrawn children, the teachers' ability to convey empathy and acceptance was a determining factor in their students' improved behavior. More recent literature has also supported the use of filial therapy training with teachers (Bratton & Landreth, 1995;Brown, 2001;Ginsberg, 1984;Landreth, 1999;White, Draper, Flynt, O'Shaughnessy, & Jones, 1997;. The teachers' ability to convey empathy and acceptance is central to the teachers and students'…”
Section: Communication Of Acceptance: a Dimension Of Empathymentioning
confidence: 99%
See 1 more Smart Citation
“…Smith (2000) found significant results on nine of sixteen hypotheses; children in the treatment group were found to have significant increases in positive self-concept as measured by the Joseph Preschool and Primary Self-Concept Screening Test (JPPSST; Joseph, 1979), as well as fewer behavioral problems as measured by mothers' reports on the Child Behavior Checklist (CBCL). In addition, Smith (2000) found that the mothers who received intensive filial therapy training displayed significant increases in their expressions of acceptance and empathy during their parent-child play times, as measured by the Measurement of Empathy in Adult Child Interactions (MEACI; Stover et al, 1971) as adapted by Bratton and Landreth (1995). Finally, Smith (2000) concluded that, intensive filial therapy is comparable in its effectiveness to intensive individual play therapy and intensive sibling group play therapy.…”
Section: Play Therapy Research With Traumatized Childrenmentioning
confidence: 99%
“…For instance, multiple research studies involving CPRT have demonstrated that filial therapy leads to increases in parents' acceptance of their children (Bratton & Landreth, 1995;Chau & Landreth, 1997;Costas & Landreth, 1999;Harris & Landreth, 1997;Kale & Landreth, 1999;Landreth & Lobaugh, 1998;Lee & Landreth, 2003;Tew, Landreth, Joiner, & Solt, 2002;Yuen, Landreth, & Baggerly, 2002). In addition, multiple studies have demonstrated that participation in CPRT increases parents' empathic behaviors toward their children (Bratton & Landreth, 1995;Carnes-Holt, 2010;Chau & Landreth, 1997;Costas & Landreth, 1999;Ferrell, 2004;Glover & Landreth, 2000;Harris & Landreth, 1997;Jang, 2000;Kidron, 2004;Lee & Landreth, 2003;Smith & Landreth, 2003;Yuen et al 2002) . Winek et al (2003) found that parents facilitated play sessions by demonstrating behaviors of acceptance and encouragement, and children facilitated play sessions by expressing emotions.…”
Section: Cprt and Experiential Family Therapymentioning
confidence: 99%